2007
DOI: 10.1111/j.1537-2995.2007.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti‐D in D– recipients transfused with D+ red blood cells

Abstract: The 22 percent rate of anti-D alloimmunization in patients requiring urgent RBC transfusion was intermediate between the rates previously reported for D- oncology patients transfused with D+ RBCs and that in immunocompetent volunteer recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 18 publications
3
108
3
1
Order By: Relevance
“…Alloimmunization to the RhD antigen on RBCs ranges from 20% to 80%, with only 3% to 10% of recipients becoming immunized to the remaining RBC antigens (eg, Kell, Duffy, Kidd), despite chronic transfusion. [3][4][5] The reason why some transfused patients but not others become alloimmunized is unclear, and factors influencing alloimmunization have been only partially defined. Immunogenetics plays some role in variability of alloimmunization to blood products, as antibody responses to certain alloantigens are confined to distinct recipient human leukocyte antigen (HLA) types.…”
Section: Introductionmentioning
confidence: 99%
“…Alloimmunization to the RhD antigen on RBCs ranges from 20% to 80%, with only 3% to 10% of recipients becoming immunized to the remaining RBC antigens (eg, Kell, Duffy, Kidd), despite chronic transfusion. [3][4][5] The reason why some transfused patients but not others become alloimmunized is unclear, and factors influencing alloimmunization have been only partially defined. Immunogenetics plays some role in variability of alloimmunization to blood products, as antibody responses to certain alloantigens are confined to distinct recipient human leukocyte antigen (HLA) types.…”
Section: Introductionmentioning
confidence: 99%
“…Because an immunization of more than 50% is not acceptable, measures to prevent exposure of patients negative for this Ag are taken whenever possible. Interestingly, studies have shown a high variability in the rate of immunization against RH1, suggesting the involvement of other factors [1,2]. A series of observations of transfused patients revealed the potential of immunization being associated with other RBC Ags; about 20 polymorphic molecules have the capacity of immunizing a significant number of recipients (but always less than 10%, which is the case for KEL1, RH3, RH4, JK1 and FY1, for others the rate is lower than 1% [3,4]), while the remaining 300 are have not been included in the statistics.…”
Section: The Immunogenicity Of Foreign Agsmentioning
confidence: 99%
“…Thus, the incidence of alloimmunization has been widely cited as 80% primarily based on studies of healthy volunteers. Two more recent retrospective analyses of patients who received D2 mismatched transfusions indicate lower rates of alloimmunization, i.e., 16 of 78 (21%) transfused patients [6] and 22 of 98 (22%) nononcological transfused patients [7].…”
Section: Introductionmentioning
confidence: 99%